Garner’s aldehyde as a versatile intermediate in the synthesis of enantiopure natural products - Passiniemi, Mikko; Koskinen, Ari M.P. (Beilstein Journal of Organic Chemistry, 2013)
Since its introduction to the synthetic community in 1984, Garner’s aldehyde has gained substantial attention as a chiral intermediate for the synthesis of numerous amino alcohol derivatives. This review presents some of the most successful carbon chain elongation reactions, namely carbonyl alkylations and olefinations. The literature is reviewed with particular attention on understanding how to avoid the deleterious epimerization of the existing stereocenter in Garner’s aldehyde.
Keywords: asymmetric synthesis; Garner’s aldehyde; natural product synthesis; L-serine